Multiple-objective optimization of hydroxyapatite-added EDM technique for processing of 316L-steel. Issue 10 (27th July 2021) - Al-Amin, Md; Abdul-Rani, Ahmad Majdi; Ahmed, Rasel; Rao, T. V. V. L. N.
ABSTRACT: Fabrication of the 316 L steel with moderate surface roughness (SR) and thin recast layer (RLT) is very difficult using both the conventional and non-traditional machining processes. Due to the stochastic behavior of electro-discharge machining (EDM) process, the machining performances significantly rely on the system variables. This research work aims to investigate the influences of EDM method variables on the machining performances during the machining of 316 L steel. Another goal is to minimize the performances by applying nano-hydroxyapatite (HA) particles in the EDM-Oil. Moreover, the optimal solutions for processing of 316 L through the NSGA-II method are proposed in this research. Followed by the pulse-on time and HA amount, ANOVA study reports peak current being the most important parameter for the responses such RLT and SR. The augment of peak current, HA amount, and pulse-on time result comparatively lower RLT and SR than the previous studies. The best 7 solutions selected from the predicted 120 solutions following the objectives are proposed generating the Pareto frontiers. Less than 10% of the validation tests errors confirm the high accuracy of the predicted solutions. The present research proposed a potential and cost-effective method for processing of 316 L steel.